Essential human virology - Louten, Jennifer (Academic Press is an imprint of Elsevier, 2016)
This textbook provides undergraduate students with a foundation in human virology by covering the structure and classification of viruses, as well as virus transmission and virus replication strategies. It also features case studies to help illustrate the cellular pathology that viruses cause in a range of human diseases.